The Effect of Hemingway Editor Application and Teacher Feedback on the Students' Writing Performance at SMAK Santo Paulus Jember - Triyanto, Septian Bagas; Sundari, Hanna; Juhana, Juhana (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigated the effect of the Hemingway Editor application and teacher feedback on students’ writing performance at SMAK Santo Paulus Jember. The study employed a quasi-experimental non-equivalent control group design with multiple measurements. Fifty-four twelfth-grade students participated and were assigned to an experimental group (n = 27) and a control group (n = 27). The control group received teacher feedback only and was assessed twice (pre-test and final post-test). The experimental group was assessed three times: pre-test, post-test 1 after using the Hemingway Editor only, and post-test 2 after receiving the combined treatment of the Hemingway Editor and teacher feedback. Students completed a procedure-text writing task, and their work was scored using an analytic rubric adapted from Jacobs et al. Descriptive statistics were used to summarize performance at each measurement point. Normality was examined using the Shapiro–Wilk test, and the analysis proceeded with non-parametric tests when the normality assumption was not fully met. The Wilcoxon Signed-Rank Test indicated a statistically significant improvement in writing performance across the relevant measurement points, and the between-group comparison at the final measurement point showed a meaningful difference favoring the experimental treatment. Overall, the findings suggest that the Hemingway Editor application can support students’ writing development, and its impact is strengthened when combined with structured teacher feedback.